FORMATION OF JOINT-STOCK COMPANIES IN UZBEKISTAN IN THE INITIAL PERIOD OF INDEPENDENCE (Scientific journal of the Fergana State University, 2024)
The article describes the history of the formation and development of joint stock business in the Republic of Uzbekistan in 1989-1996. The complexity of the stages of formation of a joint-stock business, their reasons, as well as the further deepening of reforms that led to the formation of market relations and the development of joint-stock business in the republic are shown.